Utility of the systemic inflammatory response syndrome (SIRS) criteria in predicting the onset of septic shock in hospitalized patients with hematologic malignancies - Mato, Anthony; Fuchs, Barry D.; F. Heitjan, Daniel; Mick, Rosemarie; Halpern, Scott D.; Shah, Payal D.; Jacobs, Samantha; Olson, Erin M.; Schuster, Stephen J.; Ujjani, Chaitra; Chong, Elise A.; Loren, Alison W.; et al. (Cancer biology & therapy, 2009)
Background: The systemic inflammatory response syndrome (SIRS) criteria have not been validated in patients with hematologic malignancies (HM). Objective: To determine whether daily assessment of SIRS criteria allows early identification of HM patients who will develop septic shock (SS). Design: Observational, single-center, nested case-control study. Setting: Oncology unit of a tertiary care center. Patients: 547 consecutive, hospitalized, HM subject were enrolled. Using incidence-density sampling, 184 controls were matched to 46 SS cases. Measurements: The study exposure was the SIRS score. The study outcome was the development of SS during the hospitalization. Main Results: 8.4% of subjects developed SS. SIRS scores measured 24 hours prior to SS were significantly higher in cases than in controls (2.1 vs. 1.4, p